Mechanism of ATP-sensitive K channel inhibition by sulfhydryl modification. - Trapp, S; Tucker, S; Ashcroft, F (1998)
ATP-sensitive potassium (KATP) channels are reversibly inhibited by intracellular ATP. Agents that interact with sulfhydryl moieties produce an irreversible inhibition of KATP channel activity when applied to the intracellular membrane surface. ATP appears to protect against this effect, suggesting that the cysteine residue with which thiol reagents interact may either lie within the ATP-binding site or be inaccessible when the channel is closed. We have examined the interaction of the membrane-impermeant thiol-reactive agent p-chloromercuriphenylsulphonate (pCMPS) with the cloned beta cell KATP channel. This channel comprises the pore-forming Kir6.2 and regulatory SUR1 subunits. We show that the cysteine residue involved in channel inhibition by pCMPS resides on the Kir6.2 subunit and is located at position 42, which lies within the NH2 terminus of the protein. Although ATP protects against the effects of pCMPS, the ATP sensitivity of the KATP channel was unchanged by mutation of C42 to either valine (V) or alanine (A), suggesting that ATP does not interact directly with this residue. These results are consistent with the idea that C42 is inaccessible to the intracellular solution, and thereby protected from interaction with pCMPS when the channel is closed by ATP. We also observed that the C42A mutation does not affect the ability of SUR1 to endow Kir6.2 with diazoxide sensitivity, and reduces, but does not prevent, the effects of MgADP and tolbutamide, which are mediated via SUR1. The Kir6.2-C42A (or V) mutant channel may provide a suitable background for cysteine-scanning mutagenesis studies.